2012
DOI: 10.1080/08995605.2012.672903
|View full text |Cite
|
Sign up to set email alerts
|

Review of Adaptive Training System Techniques

Abstract: The current review examined theoretical and empirical adaptive training systems research. Through our review of the literature, we identified different models of adaptive training, such as the macro, micro, aptitude-treatment interaction, and two-step approaches. Additionally, we identified different learner characteristics, such as personality and prior knowledge, that can be used as the basis for tailoring instructional content or difficulty. Finally, our review revealed that several empirical questions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In contrast to the preceding experiments, which administered feedback on a trial-by-trial basis, Experiment 4 provided observers with outcome feedback about their face matching performance (see, e.g., Kulhavy & Stock, 1989;Kluger & DeNisi, 1996;Mory, 2004;Shute, 2008;Narciss, 2008;Landsberg et al, 2012). This was delivered by providing each observer with a percentage score of the total number of their correct responses at the end of a block of trials.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the preceding experiments, which administered feedback on a trial-by-trial basis, Experiment 4 provided observers with outcome feedback about their face matching performance (see, e.g., Kulhavy & Stock, 1989;Kluger & DeNisi, 1996;Mory, 2004;Shute, 2008;Narciss, 2008;Landsberg et al, 2012). This was delivered by providing each observer with a percentage score of the total number of their correct responses at the end of a block of trials.…”
Section: Methodsmentioning
confidence: 99%
“…Many authors (Cook 2005;Landsberg et al 2012) have suggested that increased personalization (i.e. adaptive learning) gives online learning an efficiency advantage.…”
Section: Myth 2 Online Learning Is Cheap and Easy To Implementmentioning
confidence: 99%
“…All three models currently lack a theory of how individual differences in aptitude, personality, and prior knowledge affect performance (Ackerman, 1987;Landsberg et al, 2012). All three models currently lack a theory of how individual differences in aptitude, personality, and prior knowledge affect performance (Ackerman, 1987;Landsberg et al, 2012).…”
Section: Account For Effects Of Training Variables On Learning and Rementioning
confidence: 99%